Emerging technologies for biofuels production - Yusup, S. (Elsevier, 2019)
The outlook and incentive toward the development of cleaner and sustainable energy resources are growing worldwide due to the rise of fossil fuel price, depletion of petroleum resources, and environmental protection issues. Therefore, the development of biofuel technologies, that is, bio-based fuels are projected to play an essential role in the foreseeable transportation and automotive industries. Synthetic biofuels from agricultural-based origins such as biohydrogen, biogas, biogasoline, biodiesel, and green diesel will emerge as prospective fuels of tomorrow due to their excellent fuel properties and environmental friendly attributes. Thus, this book chapter focuses on the challenges and drawbacks of the existing liquid and gaseous biofuel production technologies. To overcome these challenges, advanced biofuel technologies such as steam gasification, ultrasonic and microwave intensification for biodiesel production, catalytic cracking and hydrodeoxygenation of vegetable oils for biogasoline, and green diesel have been discussed in detailed. Furthermore, critical analysis on the fundamental reaction and process optimization affecting the biofuel production has been conversed as well. This chapter also addresses the future prospective of emerging biofuel technologies that could potentially bridge with the existing biofuels technologies. Â© 2019 Elsevier Inc. All rights reserved.